Factors Influencing to Preventive Behaviors for Coronavirus Disease 2019 of Thai and Migrant Workers in Bang Sao Thong District, Samutprakarn Province - Kawitu, Kwanruen; Thansuk , Chaisit; Suksai, Narong (Journal of Nursing, Siam University, 2023)
This research aimed to examine the preventive behavior for coronavirus disease 2019 (COVID-19) and factors affecting the preventive behaviors for coronavirus disease 2019 of Thai and migrant workers in Bang Sao Thong District, Samutprakarn Province. The sample were 420 people including 210 Thai workers and 210 migrant workers who work in Bang Sao Thong district, Samutprakarn province. Samples were selected by stratified random sampling technique. The data were collected during August 2022. The research instruments were questionnaires to assess demographic characteristics, health literacy, social support, attitude, towards coronavirus disease 2019, perception towards benefits and barriers of prevention behaviors, and the prevention behaviors of coronavirus disease 2019. All research instruments were validated in terms of content validity by three experts in the field. The Content validity index (CVI) was .96. The Cronbach’s alpha coefficient reliability of the questionnaire was tested yielding values of .81 and .77 respectively. The quantitative data were analyzed using multiple regression. The results found that the worker had a high level of prevention behavior of coronavirus disease 2019 (Mean = 2.18, SD = .50). Multiple regression analysis revealed that the following factors were statistically significantly (p-value < 0.05) affected the preventive behaviors of Coronavirus disease 2019; health literacy (Beta = .134, p = .004), attitude (Beta = .234, p < .001), social support (Beta = .226, p < .001), perception in the barriers related to the coronavirus disease 2019 (Beta = -.081, p = .037) and perception in the benefit related to coronavirus disease 2019 (Beta = .244, p < .001) were able to predict the prevention behavior of coronavirus disease 2019 at 53 percentages (R2 = .533, p < .001) The study results can be used as a guideline for defining plans and activity models in accordance with society such as activities to make people more knowledgeable, cope with emerging incidents in the future, and prepare workers to be ready for new ways of life.